TM-AL-ON coating layer with improved thermal stability
The TM-AL-O-N coating that controls the oxygen content solves the thermal stability and mechanical performance of the coating under high temperature environment, and achieves the improvement of the stability and mechanical performance of the coating at high temperature.
Patent Information
- Application Number
- JP2021552860
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-21
- Filing Date
- 2020-03-09
- Publication Date
- 2025-02-05
- Estimated Expiration
- 2040-03-09
AI Technical Summary
The prior art is difficult to provide metal nitrogen oxide coatings with excellent mechanical properties, low thermal conductivity and high hardness in high temperature environments, especially for use at temperatures above 1100°C.
The TM-AL-O-N coating is prepared by controlling the oxygen content, and the TM-AL-N coating is deposited on the substrate by using the PVD method, and the oxygen flow rate is adjusted to form the TM-AL-O-N coating with a specific oxygen concentration to ensure a stable cubic phase structure is maintained at high temperatures.
The high thermal stability and mechanical properties of the coating are achieved at high temperatures, and the coating can still maintain good mechanical properties and structural stability at temperatures above 1200°C.
Smart Images

Figure 0007627047000001 
Figure 0007627047000002 
Figure 0007627047000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a coating, which comprises at least one coating layer of TM-Al-ON, exhibiting a solid solution of B1 cubic structure or a spinodal decomposition phase of cubic structure, and the oxygen concentration in the TM-Al-ON coating layer is determined in such a way that no precipitation of w-AlN phase occurs even when the coating is exposed to temperatures above 1100° C., and the elemental composition is (TM 1-x Al x )O y N z The elemental composition of the coating layer is different from that of the coating layer alone (TM 1-x Al x )N z TM 1-x Al x )N z is oxygen-free. The present invention also relates to the use of such inventive coatings in applications where the coating is exposed to temperatures above 1100°C.
[0002] In the context of the present invention, the term "high temperature" is used to refer to temperatures above 1100°C. [Background technology]
[0003] Prior Art In the scientific paper "Phase stability and elastic properties of titanium aluminum oxynitride studied by ab initio calculations" by Moritz to Baben, Leonard Raumann, and Jochen M Schneider, published in J. Phys. D: Appl. Phys. 46 (2013) 084002 (6pp), it is suggested that the mixing energy of TiAlON at 0 K is negative, i.e., Fcc-Ti 0.5 Al 0.5 N and fcc-Ti 0.5 Al 0.5It is possible that a solid solution is formed between TiAlN and O. However, this study does not provide any insight into the high-temperature stability of the cubic phase of TiAlN.
[0004] Objective of the invention It is an object of the present invention to provide coatings, including metal nitride based PVD wear resistant coatings, suitable for high temperature applications.
[0005] Metal nitride based coatings should preferably exhibit the following properties: -Maintaining the cubic metal nitride phase to achieve excellent mechanical properties; -Good oxidation resistance, - low thermal conductivity, in particular below 5 W / mK; -Good combination of toughness and hardness. Summary of the Invention
[0006] Description of the invention The object of the present invention is achieved by depositing in a controlled manner oxygen-containing transition metal aluminum nitride coatings (abbreviated TM-Al-N coatings), hereafter referred to as "TM-Al-N coatings with controlled oxygen incorporation".
[0007] TM can be one or more transition metals.
[0008] According to a preferred embodiment of the coating according to the invention, titanium is used as the transition metal, i.e. TM=Ti.
[0009] For a better understanding of the invention, an example of a coating according to the above-mentioned preferred embodiment will now be described in more detail.
[0010] Example 1: The TiAlN and TiAlON coating layers were deposited using three TiAl targets with a chemical composition of 50:50 in atomic percentage. The target materials were arc evaporated in an Oerlikon Balzers Ingenia P3e™ type coating source. The source was operated with an arc current of 190 A. The substrate temperature during the deposition of the coating layers was maintained at 450 °C. The vacuum was 3.0·10 -4 The pressure was drawn to less than 100 Pa. Nitrogen gas was used as the reactive gas, and the nitrogen partial pressure was kept at 3.2 Pa. A negative bias voltage of -40 V was applied to the substrate to be coated. For the deposition of TiAlN coating layers, no oxygen gas flow was introduced into the coating chamber. For the deposition of TiAlON coating layers, oxygen gas flow was introduced into the coating chamber. Different TiAlON coating layers with different oxygen contents were deposited by adjusting different oxygen gas flows. During the deposition of each TiAlON layer, the oxygen gas flow was kept constant. For the deposition of different TiAlON coating layers, the value of oxygen gas flow from 0 to 80 sccm was adjusted. The elemental composition of the film including O content of the deposited coating layers was measured using ERDA (Elastic Recoil Detection Analysis).
[0011] Both TiAlN and TiAlON were deposited with a cubic phase.
[0012] The thermal stability of the cubic phase was analyzed.
[0013] The coated substrates were subjected to annealing at temperatures between 800°C and 1300°C.
[0014] Example 2
[0015] The TiAlN and TiAlON coating layers were deposited using three TiAl targets with a chemical composition of 40:60 in atomic percentage. The target materials were arc evaporated in an Oerlikon Balzers Ingenia P3e™ type coating system. The source was operated with an arc current of 120 A and using the confinement technique. The substrate temperature during the deposition of the coating layers was maintained at 520 °C. The vacuum was 3.0·10 -4 The pressure was drawn to less than 100 Pa. Nitrogen gas was used as the reactive gas, and the nitrogen partial pressure was kept at 6.0 Pa. A negative bias voltage of -40 V was applied to the substrate to be coated. For the deposition of TiAlN coating layers, no oxygen gas flow was introduced into the coating chamber. For the deposition of TiAlON coating layers, oxygen gas flow was introduced into the coating chamber. Different TiAlON coating layers with different oxygen contents were deposited by adjusting different oxygen gas flows. During the deposition of each TiAlON layer, the oxygen gas flow was kept constant. For the deposition of different TiAlON coating layers, the value of oxygen gas flow from 0 to 80 sccm was adjusted. The elemental composition of the film including O content of the deposited coating layers was measured using ERDA (Elastic Recoil Detection Analysis).
[0016] Both TiAlN and TiAlON were deposited with a cubic phase.
[0017] The thermal stability of the cubic phase was analyzed.
[0018] The coated substrates were subjected to annealing at temperatures between 800°C and 1300°C. [Brief description of the drawings]
[0019] Figure caption: [Figure 1] Summary of the onset temperature of spinodal decomposition structures with fcc-cubic phase and wurtzite phase formation as a function of oxygen loading. (Data extracted from XRD patterns). [Diagram 2] XRD stacked as a function of annealing temperature for AlTiN films, w-AlN is already precipitated at 1000 °C (black arrows). [Diagram 3] XRD stacked as a function of annealing temperature for AlTiN with 13 at.% oxygen. Surprisingly, w-AlN precipitates at 1300 °C. [Figure 4] XRD stacked as a function of annealing temperature for AlTiN with 13 at.% oxygen. X-axis is on the same scale as in Fig. 2. [Diagram 5] STEM image of the AlTiN film in its deposited state. [Figure 6] STEM image of the spinodal decomposition structure of an AlTiN film annealed at 900°C. [Figure 7] STEM image of an AlTiN film annealed at 1000°C - the white areas show that Al is segregated uniformly throughout the structure. [Figure 8] STEM image of an AlTiN film annealed at 1000°C. Higher magnification compared to Figure 7. [Figure 9] STEM image of as-deposited AlTiON film with 13 at.% oxygen. [Figure 10] STEM image of the spinodal decomposition structure of an AlTiON film with 13 at.% oxygen annealed at 900°C. [Figure 11] STEM image of the spinodal decomposition structure of an AlTiON film with 13 at.% oxygen annealed at 1200°C. [Figure 12] STEM image of an AlTiON film with 13 at.% oxygen annealed at 1300°C - the white areas indicate Al segregation that occurs preferentially at the grain boundaries. [Figure 13] STEM image of an AlTiN film annealed at 1300°C. Higher magnification compared to Figure 12. [Figure 14] STEM image of an AlTiN film annealed at 1300°C. Higher magnification compared to Figure 13. [Figure 15]Atom probe tomography reconstruction of Al atoms within a 160 nm long tip cut from an as-deposited AlTiN film. The dots represent Al atoms. The distribution of Al atoms is random. [Figure 16] Atom probe tomography reconstruction of Al atoms within a 160 nm long tip cut from an AlTiN film annealed at 900 °C. The dots represent Al atoms. Segregation of Al atoms within the structure begins. [Figure 17] Atom probe tomography reconstruction of Al atoms within a 160 nm long tip cut from an AlTiN film annealed at 1000 °C. The dots represent Al atoms. Segregated structures are visible. [Figure 18] Atom probe tomography reconstruction of Al atoms within a 160 nm long tip cut from an as-deposited 13 at.% oxygen AlTiON film. The dots represent Al atoms. The layer effect is visible when the sample is rotated during deposition. Apart from the layering due to rotation, the distribution of Al atoms is random. [Figure 19] Atom probe tomography reconstruction of Al atoms within a 160 nm long tip cut from an AlTiON film with 13 at.% oxygen annealed at 900 °C. The dots represent Al atoms. Layering due to sample rotation during deposition is enhanced by annealing. [Figure 20] Atom probe tomography reconstruction of Al atoms within a 160 nm long tip cut from an AlTiON film with 13 at.% oxygen annealed at 1200 °C. The dots represent Al atoms. [Figure 21] Atom probe tomography reconstruction of Al atoms within a 160 nm long tip cut from a 13 at.% oxygen AlTiON film annealed at 1300 °C. The dots represent Al atoms. On the left side of the picture, segregation of Al atoms to the grain boundary regions can be seen. [Figure 22] Analysis of compositional distribution within atom probe tomography reconstructions of as-deposited AlTiN films and comparison with binomial random distribution. The Pearson correlation coefficient (μ) is close to zero, indicating that Ti, Al, and N are distributed in a near-random manner. [Figure 23]Analysis of compositional distribution within atom probe tomography reconstructions of AlTiN films annealed at 900 °C and comparison with binomial random distribution. The Pearson correlation coefficient (μ) between Ti and Al is close to 1, indicating a segregated structure. [Figure 24] Analysis of compositional distribution within atom probe tomography reconstructions of AlTiN films annealed at 1000°C and comparison with binomial random distribution. The Pearson correlation coefficient (μ) between Ti and Al is close to 1, indicating a segregated structure. [Diagram 25] Analysis of compositional distribution within atom probe tomography reconstructions of as-deposited AlTiON films with 13 at.% oxygen and comparison with binomial random distribution. The small Pearson correlation coefficients (μ) indicate that Ti, Al, and N are distributed in a near-random manner. [Figure 26] Analysis of compositional distribution within atom probe tomography reconstructions of AlTiON films with 13 at.% oxygen annealed at 900 °C and comparison with binomial random distribution. The Pearson correlation coefficient (μ) for Al is close to 1, indicating segregation of Al. [Figure 27] Analysis of compositional distribution within atom probe tomography reconstructions of AlTiON films with 13 at.% oxygen annealed at 1200 °C and comparison with binomial random distribution. The Pearson correlation coefficient (μ) for Al is close to 1, indicating segregation of Al. [Figure 28] Analysis of compositional distribution within atom probe tomography reconstructions of AlTiON films with 13 at.% oxygen annealed at 1300°C and comparison with binomial random distribution. The Pearson correlation coefficient (μ) of Al and Ti is close to 1, indicating a segregated structure. [Figure 29]Overview of phase structure as a function of oxygen content and annealing temperature for films deposited with Ti50Al50 targets (data extracted from XRD patterns). Cubic solid solutions are shown by filled boxes, spinodal decomposition structures with fcc-cubic phases by half-filled boxes, and secondary phase nucleation and growth by filled circles. The boundary of wurtzite phase formation is shown by the "green" w-AlN line. Above 20 at.% O, the thermal stability of the spinodal decomposition structures is limited due to the formation of secondary phases, especially TiO2. The films are removed from the substrate and powdered before annealing. The change in annealing conditions explains the detection of α-Al2O3 in the 13 at.% O sample after annealing at 1200 °C, compared to the annealing of the films in Figures 3 and 4, whereas no α-Al2O3 was detected. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] All measurements were performed on samples coated with a Ti50Al50 target, but similar results are expected for other realistic target compositions (ranging from Ti20Al80 to Ti80Al20). It is preferred to have more than 5 at% oxygen in the system. However, oxygen atomic percentages greater than 25 at% should generally be avoided, preferably percentages greater than 20 at% should be avoided, and most preferably the oxygen percentage should be at most greater than 18 at%.
[0021] Figure 1 shows the X-ray diffraction results of three types of coated samples after annealing in a vacuum atmosphere at 800°C, 900°C, 1000°C, 1100°C, and 1300°C for 30 minutes. The three types of coated samples correspond to: 1. O content = 0 at.% (y = 0) (Ti 0.5 Al 0.5 )O y N z The samples coated with Ti 0.5 Al 0.5N coated sample (deposited without introducing oxygen gas flow into the coating chamber). 2. When all elements (Ti, Al, O, N) are considered in determining the elemental composition, the O content is 8 at.% (Ti 0.5 Al 0.5 )O y N z the sample coated with, i.e., y = 0.16 (deposited with oxygen gas flow introduced in the coating chamber). 3. Ti with O content = 13 at.% 0.5 Al 0.5 O y N z The samples coated with , i.e., y = 0.26 (deposited with oxygen gas flow introduced in the coating chamber).
[0022] Ti 0.5 Al 0.5 In the N coating layer, the wurtzite phase of aluminum nitride (abbreviated as w-AlN) is already precipitated at 1000°C. 0.5 Al 0.5 O y N 1-y In the oxygen-containing coating layer of this type, w-AlN precipitates at temperatures higher than 1100°C, as shown in Figure 1. In Figure 1, Ti with y=0.16 is shown. 0.5 Al 0.5 O y N 1-y At 1200℃, Ti with y=0.26 0.5 Al 0.5 O y N 1-y In this case, w-AlN precipitates at 1300℃.
[0023] Ti 0.5 Al 0.5 The X-ray diffraction patterns of the N coating layer as deposited and after annealing at 800 °C, 900 °C, 1000 °C, and 1100 °C are shown in Figure 2.
[0024] Ti of y=0.26 0.5 Al 0.5 Oy N 1-y X-ray diffraction patterns of the coating layer as deposited and after annealing at 800°C, 900°C, 1200°C, and 1300°C are shown in Figure 3.
[0025] The mechanical properties of the coating layer were investigated by nanoindentation. 0.5 Al 0.5 O y N 1-y The films had a hardness of 28-32 GPa and an elastic modulus (also called Young's modulus) of 400-470 GPa after deposition.
[0026] TM 1-x Al x O y N z Introducing oxygen into the structure to form the structure resulted in surprisingly high thermal stability.
[0027] TM 1-x Al x O y N z At 13at.% oxygen concentration (y=0.26), TM 1-x Al x The thermal stability compared to N was significantly improved, so that the cubic spinodal decomposition phase could be maintained up to temperatures of 1200 °C.
[0028] In this way, the cubic-structured spinodal decomposition phase with excellent mechanical properties became stable in a higher temperature range (even 200°C above -900°C to 1200°C) by controlling the introduction of oxygen, as shown in Figure 1.
[0029] For this reason, the TM of the present invention 1-x Al x O y N z It is concluded that the coating layer can be very useful for high temperature applications, especially if the oxygen concentration in the coating layer after deposition is about 13%.
[0030] Samples coated with Ti40Al60 targets according to Example 2 were similarly investigated by X-ray after annealing in vacuum at 800°C, 900°C, 1000°C, 1100°C, 1200°C, and 1300°C for 30 minutes, respectively, resulting in the following observations regarding the formation of w-AlN: 1. O content = 0 at.% (y = 0) (Ti 0.4 Al 0.6 )O y N z The samples coated with Ti 0.4 Al 0.6 The N-coated sample (deposited without introducing oxygen gas flow into the coating chamber) shows the formation of w-AlN after annealing up to 1100 °C. 2. When all elements (Ti, Al, O, N) are considered in determining the elemental composition, the O content is 6 at.% (Ti 0.4 Al 0.6 )O y N z The sample coated with, i.e., y = 0.12 (deposited with oxygen gas flow introduced in the coating chamber) shows the formation of w-AlN after annealing up to 1300 °C, i.e., 200 °C higher compared to the sample without oxygen. 3. When all elements (Ti, Al, O, N) are considered in determining the elemental composition, the O content is 8 at.% (Ti 0.4 Al 0.6 )O y N z The sample coated with, i.e., y = 0.16 (deposited with oxygen gas flow introduced in the coating chamber) shows the formation of w-AlN after annealing up to 1300 °C, i.e., 200 °C higher compared to the sample without oxygen. 4. When all elements (Ti, Al, O, N) are considered in determining the elemental composition, Ti has an O content of 22 at.%. 0.4 Al 0.6 )O y N zThe sample coated with, i.e., y = 0.44 (deposited with oxygen gas flow introduced in the coating chamber) shows the formation of w-AlN after annealing up to 1300 °C, i.e., 200 °C higher compared to the sample without oxygen.
[0031] Similar behavior can be expected for other TiAlN coatings with different Ti:Al ratios and other types of TM-AlN coatings such as CrAlN, VaAlN, and NbAlN.
[0032] Coatings according to the invention are particularly useful for coating surfaces of tools or parts which are used in applications involving exposure of the tool or part surface to temperatures in excess of 1100°C.
[0033] The inventors propose to use these coatings for example to protect and improve the performance of parts or tools used in the following applications: (a) the high pressure turbine of an aircraft engine or the sealing of the high pressure turbine of an aircraft engine; (b) Machining of difficult-to-cut materials, such as nickel-based superalloys like Inconel 718, (c) High temperature forming operations such as rolling and forging carried out at temperatures above 1100°C.
[0034] Further insight into the structural evolution of the TiAlN and TiAlON coatings is provided by analyzing the as-deposited and annealed samples using scanning transmission electron microscopy (STEM) and atomic force microscopy (APT).
[0035] STEM images of as-deposited TiAlN (Figure 5) and TiAlON (Figure 9) show a columnar structure. After annealing to 900 °C, spinodal decomposition structures show that the columnar structure was maintained for TiAlN (Figure 6) and TiAlON (Figure 10). When the TiAlN coatings were annealed to 1000 °C, the segregation of w-AlN was seen in the STEM images (Figures 7 and 8 at higher magnification) as bright features distributed throughout the grains. On the other hand, after annealing to 1300 °C to form w-AlN, TiAlON shows preferential segregation at the grain boundaries as evident in the STEM images (Figures 12 and 13 and 14 at higher magnification).
[0036] Atom probe tomography shows a random structure of Al atoms in the deposited TiAlN (Figure 15). Annealing to 900°C (Figure 16) and 1000°C (Figure 17) reveals the segregation of Al throughout the tip.
[0037] TiAlON shows that as deposited it is layered due to the effect of substrate rotation during deposition (Fig. 18). This layering effect is enhanced as the Al content increases at the rotation boundary after annealing to 900 °C (Fig. 19) and 1200 °C (Fig. 20). After annealing to 1300 °C, a strong segregation of Al is seen in the left part of the reconstructed tip (Fig. 21).
[0038] Compositional distribution analysis of atom probe tomography data is a further technique following decomposition. This technique and the application of the Pearson coefficient (μ) are described by MP Moody et al. in the journal Microscopy Research and Technique volume 71, pages 542-550 in the journal Microscopy Research and Technique. As-deposited TiAlN (Figure 22) and TiAlON (Figure 25) have Pearson coefficients (μ) close to 0, indicating a solid solution with a near-random distribution. TiAlON has a slightly higher μ(Al) value due to its layered structure during deposition, as seen in the APT reconstruction (shown in Figure 18).
[0039] After annealing to 900 °C, the TiAlN coating has Pearson coefficients for Ti and Al close to 1, indicating segregation in the spinodally decomposed structure (Figure 23). TiAlON (Figure 26) annealed at the same temperature has a lower value of the Pearson coefficient for Ti, indicating less segregation compared to TiAlN.
[0040] The decomposed structures are characterized by Pearson coefficients for Ti and Al close to 1, as seen for TiAlN annealed to 1000 °C (Figure 24) and TiAlON annealed to 1300 °C (Figure 28).
[0041] Layers with the same chemical composition can have different crystalline phases, in particular a layer according to claim 1 can exhibit a solid solution with a B1 cubic structure or a layer according to claim 2 can exhibit a spinodally decomposed phase with a cubic structure. The growth of layers and the formation of crystalline phases in PVD (Physical Vapor Deposition) is a complex process that can be influenced by several factors. The most important parameters apart from the composition are the temperature, the process pressure, the bias and the degree of ionization. Furthermore, the thermal history has a decisive influence, which can change the phase structure if the layer is kept at a tempering temperature above the coating temperature. This is the case for the difference between the substrate according to claim 1 and the substrate according to claim 2, as can also be seen in the text of FIG. 1: In the coated state as described in claim 1, a single-phase cubic structure is present (solid solution). After the tempering temperature, preferably in the range of 800°C to 900°C to 1300°C depending on the O content, spinodal segregation to a cubic structure occurs. Therefore, a spinodal decomposition phase having a cubic structure as described in claim 2 can be produced.
[0042] TiAlON coatings according to preferred embodiments of the present invention have been found to exhibit grains with grain sizes, also referred to as domain sizes, in the range of 5-50 nm, preferably 15-35 nm, as determined by XRD (X-ray diffraction). This quantification was done according to standard methods (Sherrer's equation) based on the XRD patterns in Figure 3.
[0043] The TiAlON coating preferably has the following near random distribution of atoms: i. Characterized by a Pearson coefficient of Ti (μTi) less than 0.20, ii. characterized by a Pearson coefficient of Al (μAl) of less than 0.20; iii. It is characterized by a Pearson coefficient of N (μN) less than 0.20.
[0044] FIG. 25 shows the concentration distribution according to data obtained by atom probe tomography.
[0045] The TiAlON coating preferably includes a periodic modulation of the composition, and in particular of the Al content. Furthermore, the composition modulation preferably has a periodicity of 5-30 nm, preferably about 10 nm. This can be seen in particular in Figures 18 and 19.
Claims
1. (TM 1-x A x ) O y N 1-y wherein x is the aluminum content in atomic fraction when only aluminum and TM are considered in determining the elemental composition in atomic percentage, y is the oxygen content in atomic fraction when only O and N are considered in determining the elemental composition in atomic percentage, and TM is one or more transition metals; T = T; x=0.5, y is in the range of 0.25<y<0.35, which provides increased thermal stability such that precipitation of the w-AlN phase does not occur when at least the coated surface of the coated substrate is exposed to a temperature higher than 1100° C. and lower than 1300° C. 1-x A x O y N 1-y A coated substrate, characterized in that it corresponds to a value of oxygen concentration in the coating layer.
2. The coated substrate of claim 1 , wherein the substrate is a forming tool.
3. The coated substrate of claim 1 , wherein the substrate is a cutting tool.
4. 2. The coated substrate according to claim 1, characterized in that the substrate is a part of a high pressure turbine of an aircraft engine or a sealing of a high pressure turbine of an aircraft engine.
5. The Ti 1-x A x O y N 1-y 5. Coated substrate according to any one of claims 1 to 4, characterized in that the coating layer exhibits grains with a grain size in the range of 5 to 50 nm, preferably 15 to 35 nm, preferably obtained by XRD (X-Ray Diffraction).
6. 3. Use of the coated substrate according to claim 2, characterized in that the forming tool is used in high temperature forming operations.
7. 4. Use of the coated substrate according to claim 3, characterized in that the cutting tool is used in cutting operations involving the machining of difficult-to-cut materials.
Citation Information
Patent Citations
Nano composite cutting tool coating of multilayer structure
CN105112858A
Dental instrument
JP1979041596A
Cutting tool insert and its manufacturing method
JP2004050403A
Coating for high temperature applications with tribological stress
JP2018111828A
Reduced-friction coatings
US20090074522A1